A new approach to improving flame retardancy, smoke suppression and anti-dripping of PET: Via arylene-ether units rearrangement reactions at high temperature. (23rd October 2015) - Guo, De-Ming; Fu, Teng; Ruan, Chao; Wang, Xiu-Li; Chen, Li; Wang, Yu-Zhong
Abstract: In order to avoid the serious melt-dripping problems caused by conventional phosphorus flame retardants, a new arylene-ether containing monomer named 2, 2′-(4, 4′-(1, 4-phenylenebis(oxy))bis(4, 1-phenylene))bis(oxy) diethanol (PBPBD) was synthesized and introduced into the PET main-chain via condensation polymerization. With the incorporation of arylene-ether units, the thermal stability and the char residue from combustion of flame-retardant-element-free copolyesters containing PBPBD (BDx PETs) increased dramatically. However, the crystallinity and melting temperature of these copolymers were lower than the same quantities for PET. Thermal degradation kinetic was investigated using the Ozawa-Flynn-Wall method, which illustrated that the apparent activation energy for decomposition of the copolyesters was enhanced with increasing the conversion and the content of PBPBD. Py-GC/MS results showed that the PBBPD structural units undergo rearrangement reactions at high temperature, and ultimately form conjugated heteroaromatic structures, which lead to the formation of stable char residues with unique "stick-shaped" micro-morphology. Due to these rearrangement reactions, BDx PETs showed an expected flame retardant performance and a reduction in smoke generation during combustion. For example, the LOI value for BD10 PET was 28.4, and the total smoke production (TSP) was 10.4 m 2, much smaller than that for PET, 18.8 m 2 . Moreover, melt-dripping was restricted. Graphical abstract: Highlights: The arylene-ether containing unit is introduced into PET main-chain. The arylene-ether units improved the copolyester's thermal stability and char residue. The arylene-ether units form conjugated heteroaromatic structures via rearrangement. The heteroaromatic structures endow copolyesters with good flame retardant performance. These copolyesers show low smoke release and anti-dripping behaviors.